Insoluble Polymers in Solid Dispersions for Improving Bioavailability of Poorly Water-Soluble Drugs - Tran, Thao T.D. (Polymers (Basel), 2020)
In recent decades, solid dispersions have been demonstrated as an effective approach for improving the bioavailability of poorly water-soluble drugs, as have solid dispersion techniques that include the application of nanotechnology. Many studies have reported on the ability to change drug crystallinity and molecular interactions to enhance the dissolution rate of solid dispersions using hydrophilic carriers. However, numerous studies have indicated that insoluble carriers are also promising excipients in solid dispersions. In this report, an overview of solid dispersion strategies involving insoluble carriers has been provided. In addition to the role of solubility and dissolution enhancement, the perspectives of the use of these polymers in controlled release solid dispersions have been classified and discussed. Moreover, the compatibility between methods and carriers and between drug and carrier is mentioned. In general, this report on solid dispersions using insoluble carriers could provide a specific approach and/or a selection of these polymers for further formulation development and clinical applications.